TRANSLATION OF PHRASEOLOGISMS IN THE NOVELS OF VASYL STEFANYK - Tkachivska, M. R.; Tkachivskyi, V. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2022)
The article researches the translation of phraseological units into the German language. The material of the research is the German translation of Stefanyk’s novels carried out by E. Zalevski through the Russian language. Based on the scientific research of national and foreign scientists, the article analyzes the features of the translation of phraseological units and the difficulties associated with it. In the course of the study, the emphasis is put on the importance of using phraseological synonymous series facilitating the selection of semantic equivalents. Denotation replacement usually leads to the replacement of imagery, but preserves the author’s intention. Special attention is paid to the translation of biblical texts. Since the Bible serves as their common source, in most cases, and in many languages, it is possible to choose a complete biblical phraseological counterpart with preservation of denotation and connotation. Dialect phraseology – one of the little-studied spheres of translation studies – has a special place in the scientific research. Although the emotionally colored Pokuttia dialect adds authenticity and expressiveness to the speech of Stefanyk’s characters and enhances the way one imagines their lives, its reproduction poses considerable difficulties for the translator. The following basic phraseological and non-phraseological methods of translation are distinguished for the translation of dialectal phraseology: full/partial equivalent, tracing, explanation, elimination, introduction of a vivid metaphor, borrowing of a phraseological unit from a third language, transplantation and stylization. The article emphasizes the priority of the first four methods of translation. The translator’s analysis of phraseological units of the Pokuttia dialect proves the loss of dialect markers, which has a systemic nature and leads to a change in the translation of the characters’ features of speech and loss of authenticity. At the same time, the opinion about the importance of preserving the originality of the characters’ speech with the help of its marking in translation with everyday and colloquial speech units, as well as the use of stylization, is accepted.